Supercapacitor Cell Performance with Bacterial Nanocellulose and Bacterial Nanocellulose/Polybenzimidazole Impregnated Membranes as Separator - Hristo Penchev; Galia Ivanova; Venelin Hubenov; Ivanka Boyadzieva; Desislava Budurova; Filip Ublekov; Adriana Gigova; Antonia Stoyanova (Membranes)
Supercapacitors are advanced energy storage devices renowned for their rapid energy delivery and long operational lifespan, making them indispensable across various industries. Their relevance has grown in recent years due to the adoption of environmentally friendly materials. One such material is bacterial nanocellulose (BNC), produced entirely from microbial sources, offering sustainability and a bioprocess-driven synthesis. In this study, BNC was synthesized using a symbiotic microbial community. After production and purification, pristine BNC membranes, with an average thickness of 80 microns, were impregnated with an alkali-alcohol meta-polybenzimidazole (PBI) solution. This process yielded hybrid BNC/PBI membranes with improved ion-transport properties. The BNC membranes were then doped with a 6 M KOH solution, to enhance OH− conductivity, and characterized using optical microscopy, ATR FT-IR, XRD, CVT, BET analysis, and impedance spectroscopy. Both BNC and BNC/PBI membranes were tested as separators in laboratory-scale symmetric supercapacitor cells, with performance compared to a commercial Viledon® separator. The supercapacitors employing BNC membranes exhibited high specific capacitance and excellent cycling stability, retaining performance over 10,000 charge/discharge cycles. These findings underscore the potential of BNC/KOH membranes for next-generation supercapacitor applications.